The Application of Inquiry Intelligent Tutoring System in Biology Practicum - Muhammad Lukman Baihaqi Alfakihuddin; Surahman, Ence; Haryani, Faradillah (Universitas Pendidikan Ganesha, 2022)
Implementing Distance Learning (PJJ) caused by the COVID-19 pandemic in Indonesia has triggered a shift in education from traditional to digital on various fronts, including practicum. The virtual laboratory can be an alternative to practical learning. It still has several areas for improvement, such as the unavailability of direct feedback. It is not optimal for improving higher-order thinking skills. This study aims to analyze the effectiveness of the Inquiry Intelligent Tutoring System (Inq-ITS) in improving Biology learning outcomes. This research is quantitative and uses quasi-experimental techniques. This research will be applied to students of the Faculty of Engineering, Sampoerna University. Quasi-experimental research methods were used to answer research questions. Data collection techniques use several instruments: pretest, posttest, and practicum results reports. Data analysis using N-gain. From the results of calculating the product's effectiveness, an N-gain of 0.76 is obtained. Therefore, Inq-ITS is very effective in improving Biology learning outcomes. This research is still limited to the Inq-ITS application. It is necessary to carry out further research on ITS by measuring using other applications. This research implies that students are better able to solve HOTs questions and make better practicum reports.